ANALISIS SENTIMEN TWITTER TERHADAP BITCOIN DAN CRYPTOCURRENCY BERBASIS PYTHON TEXTBLOB - Rizky Parlika; Sunu Ilham Pradika; Amir Muhammad Hakim; Kholilul Rachman N M (Jurnal Ilmiah Teknologi Informasi dan Robotika, 2020)
Cryptocurrency technology is currently very developed, marked by the number of people who want to participate to become part of it. One of the famous cryptocurrency is Bitcoin. However, for some people, they certainly do not understand what Bitcoin is and how it works. So, it makes them hesitate to participate in becoming a part of this technology. So it needs to be made a sentiment analysis about this technology so that it can provide knowledge of what actually Bitcoin is. Through Twitter, sentiment analysis can be done to find out how many people think about Bitcoin. This can be done by utilizing the API provided by Twitter to collect data in the form of tweets. Then, do a sentiment analysis using the Python library to classify a tweet as positive, negative, or neutral. From the results of the classification using a dataset of 3433 data, it was found that 41.3% were classified positively, 44.9% were neutral, and 13.7% were negative. Then, for the visualization of the whole opinion of people about Bitcoin can be formed by using Word Cloud so that only important words will appear relating to Bitcoin. It is hoped that after this research can be seen how people, especially Twitter users, think about Bitcoin. Keywords - Bitcoin, Textblob, Cryptocurrency, Word Cloud, NLP